The Adoption of Web-Based Learning in the Teaching and Learning of Accounting in South African Secondary Schools - Tesfanesh Kassa Debusho; Patricia Namayammu Mokgosi; Margaret Kholiwe Ntsana (Journal of Education and Learning Technology)
Teachers face several challenges when adopting web-based learning to teach Accounting in South African schools. Therefore, a need exists for support and capacity building of Accounting teachers to effectively implement web-based collaborative learning in South African schools. This study sought to investigate the factors that affect the use of Web-Based Learning (WBL) in the teaching of Accounting subjects in the Capricorn District within the Limpopo Province, South Africa. A mixed-method approach framed within a pragmatic paradigm was adopted for this research study. However, only the quantitative data was presented herein.The iinvestigation was conducted with the participation of 104 participants comprising accounting subject teachers and head of departments (i.e., convenience sampling). The data was collected from the participants using a web-based survey questionnaire. To analyse the data, used descriptive research approach and SPSS version was employed. The Technology Acceptance Model and the Theory of Reasoned Action were adopted as theoretical frameworks to investigate factors affecting the use of WBL in the teaching of accounting subject in selected schools. The study’s findings revealed that perceived usefulness and perceived ease of use, subjective norm or social influence, attitudes toward computer usage, and self-confidence affect the use of WBL in the teaching and learning of Accounting in the investigated schools. Moreover, the findings confirmed the hypothesis that was developed in this study.